Estoque de nutrientes do solo e frações oxidáveis e húmicas da matéria orgânica em sistemas de cultivo da cana-de-açúcar - Silva, Adeilson Nascimento da (2020)
Soil carbon represents an important part of organic material, thus, changes in its dynamics can cause greater derivation of gases into the atmosphere, a relevant fact in the study of climate change. Therefore, the objective of this study was to evaluate how changes in the nutrient stock and in the dynamics of soil organic matter in sugarcane cultivation in the Pantanal highlands that adopt the harvest without burning plant biomass and use stillage as part fertilization of the crop. Three areas were evaluated, each with a management system, and the native forest as a non-anthropized environment. The studied areas were: i) sugarcane without burning in the pre-harvest and without vinasse (SV); ii) sugarcane without pre-harvest burning with vinasse (CV); iii) sugarcane with pre-harvest burning and native forest as a reference area (MN). In these areas, two hectares were delimited, where semi-preserved soil sampling was carried out with five replications at depths 0.0 to 0.05, 0.05 to 0.10 and 0.10 to 0.20 m. Routine chemical analysis was performed, and the stock of nutrients: calcium, potassium, phosphorus, magnesium, total nitrogen in the respective layers. The calculation performed to obtain the stock was taken into account the apparent soil density of the native forest area. Chemical fractionation of soil organic matter (MOS) was carried out, with fractions oxidizable (F1, F2, F3 and F4), and humic substances (C-AF, C-AH, CH), as well as total organic carbon (COT ) and the organic carbon stock (C) in the humic fractions. The CQ cultivation system had lower levels of stored TOC. The CV cultivation system had higher nutrient accumulations when compared to the CQ area, except for Ca and NT. The use of vinasse provided better chemical and physical biological conditions to the system regarding the accumulation of nutrients in the soil. The fractionation of oxidizable carbon, the fraction considered the most labile (F1), did not differ between areas, except in the 0.0 to 0.05 m layer between CV and SV. The CV had a predominance of F3, a fraction of medium lability. With fractionated humic substances, humic acid predominated in the 0.0 to 0.05 m layer, highlighting the CV area with the highest content (23.2 g kg-1 of C-HA), and in the layers 0.05 - 0.10 and 0.10 - 0.20 m the humine fraction predominated, where the areas CV and SV 38.5 and 43.8 g kg-1 CH in the layer 0.05 - 0.10 m and 35 , 5 and 48.5 g kg-1 of CH in the 0.10 - 0.20 m layer. The fraction of fulvic acid was not observed difference between the areas.